Development of a computer aided decision support system for the design of drip irrigation laterals - Karatt, K. K. Shaheemath; Veerabadran, Ravikumar; Kannan, Balaji; Duraisamy, M. R.; Ganapati, Patil Santosh (Journal of Aridland Agriculture, 2023)
Drip Design Check (DDC) is a powerful software solution designed to assist irrigation system designers in evaluating the effectiveness of their drip irrigation designs for non-uniform slope conditions. The software makes use of recent developments in drip design methods as well as the advancements in software development methodologies for simulating and optimizing the design of laterals. The software features an easy-to-use interface that allows users to input key design parameters, including slope details, discharge rate of drippers, length of lateral, spacing between drippers and pressure head at the inlet of lateral. The software calculates relative pressure head variation (vh) and pressure head values at each outlet. The software evaluates the goodness of the design based on the allowable relative pressure head variation. Simulation of lateral also considers dripper connection losses. Variations in lateral and dripper configurations are handled by the software in line with the intuition of the user’s perceptions. Hence, data input is simple and easy. The software can be used to analyse numerous design alternatives and to identify the most appropriate design. DDC has undergone several tests using different typical sample data and hence its accuracy and reliability are more. Demonstrations were conducted for designers to assess the user friendliness of the drip simulation software, and we received favourable feedback from them. In summary, Drip Design Check is a useful and reliable tool for the irrigation industry to check the goodness of lateral design.